A consecutive synthesis of spirocyclopentanes from 2, 4-dioxo-arylbutanoates, malononitrile and vicinal dicarbonyl compounds. Issue 18 (17th September 2021) - Parhami, Azadeh; Yavari, Issa
Abstract: A consecutive synthesis of highly-functionalized spirocyclopentane derivatives via sequential reaction of ethyl 2, 4-dioxo-arylbutanoates, malononitrile (or ethyl 2-cyanoacetate), and vicinal dicarbonyl compounds, such as ninhydrin, isatin, and acenaphthenequinone in MeCN at room temperature is described. The advantages of this protocol are short reaction time, simple procedure, and good yields. Graphical Abstract: UF0001